Strategies to converge local water managing practices and water policy with water science and engineering in Southern and Eastern Mediterranean countries - Dudeen B. (Harmonization and integration of water saving options. Convention and promotion of water saving policies and guidelines, 2007)
Policy making in developing countries is still ad hoc and does not fully use research based information. One of the main reasons for this is the weak linkages between researchers, especially the policy research community, and policy makers. Development of local and regional actions to narrow the gap between research community and other social solidarities, especially the policy makers, is desperately needed and of paramount importance. This paper is mainly dependent on the ideas extracted from a critical review done recently by a panel of experts for EU-INCO for evaluating water research projects with relevance to Integrated Water Resources Management (IWRM) approach done in the period 1994-2006 (FP4-FP6).
5. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2006/05/03-07, Malta (Malta)